2011
DOI: 10.1177/0022034511429570
|View full text |Cite
|
Sign up to set email alerts
|

An X-ray Microtomographic Study of Natural White-spot Enamel Lesions

Abstract: White-spot enamel lesions are an early presentation of dental caries and are ideally managed by non-invasive procedures. The aim of this study was to characterize white-spot enamel lesions by x-ray microtomography. In particular, mineral content across the lesion from the surface to the base of the lesion was measured and surface layers defined. Molars with long buccal white-spot enamel lesions were collected, photographed, and each sectioned to produce 3 500-µm-thick sections. The sections were mounted and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…The observation that active lesions were better infiltrated than inactive lesions does not come as a surprise. Active enamel lesions have bigger pores and less mineralized surface layers than inactive enamel lesions [Thylstrup et al, 1994;Cochrane et al, 2012]. This allows the infiltrant to penetrate deeper and fill out more of the body of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that active lesions were better infiltrated than inactive lesions does not come as a surprise. Active enamel lesions have bigger pores and less mineralized surface layers than inactive enamel lesions [Thylstrup et al, 1994;Cochrane et al, 2012]. This allows the infiltrant to penetrate deeper and fill out more of the body of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated that surface mineral levels only decreased slightly but subsurface mineral levels declined considerably 9,10) , while comparison of active and inactive white spots failed to show any significant differences in surface mineral levels (g/cm 3 ) 10) . However, when the white spots are continuously exposed to plaque accumulation and other factors that trigger caries progression, the surface mineral level declines until the lesions become porous, resulting in decreased enamel surface hardness followed by partial surface decay classified as ICDAS code 3 caries.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies on early-stage enamel caries (white spots) in extracted teeth investigated depthrelated changes in mineral content by creating mineral profiles based on transverse microradiography (TMR) and micro computed tomography (CT) images 9,10) . These studies demonstrated that surface mineral levels only decreased slightly but subsurface mineral levels declined considerably 9,10) , while comparison of active and inactive white spots failed to show any significant differences in surface mineral levels (g/cm 3 ) 10) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors also found that examination of initial caries in the enamel using micro-CT showed no significant differences between the lesions clinically qualified as active and inactive. Only the active lesions had a more porous surface in comparison with inactive lesions [7]. Another pathology imaged in the micro-CT scan is the dentinal dead tracts extending from the exposed, damaged surface of the molar around the tooth neck to the pulp.…”
Section: Carious Tissues and Cavity Preparation Assessment In Micro-ctmentioning
confidence: 99%